What place does elite sport have for women? A scoping review of constraints - Fraser, Kotryna K.; Kochanek, Jill (Frontiers in Sports and Active Living, 2023)
Introduction Despite increases in participation and raised attention for girls and women in sports, female sport is still based on male evidence that ignores gendered differences and experiences of unequal treatment and marginalization from grassroots to elite sport. This paper aimed to critically interrogate the place that women have in the male preserve of elite sport by conducting a two-part study. Methods First, we provided a brief sociohistorical analysis of gender in sport as a means to move away from a decontextualized and universalized approach dominating in sport science literature. We then conducted a scoping review following PRISMA-ScR guidelines to synthesize existing sport science literature that implemented Newell's constraints-led approach to examine elite performance. Results Ten studies were identified, none of which collected demographic data or centred on female athletes and the effects of sociocultural constraints on their performance. Instead, male-centred, masculine sports and physiological profiles dominated the identified studies. Discussion We discussed these results considering critical sport research and cultural sport psychology literature to offer an integrative, interdisciplinary approach to advocate for more culturally sensitive, context-specific interpretations of gender as a sociocultural constraint. We put forth a call to action for sport science researchers, practitioners, and decision-makers to move away from implementing male evidence in female sport and attend to the unique needs of female athletes. Practical suggestions aimed to help stakeholders reimagine elite sport by celebrating these [potential] differences as strengths for promoting gender equity in sport.